Multiple-beam focal-plane dual-band fabry–pérot cavity antenna with reduced beam degradation - Lima, E. B.; Costa, J. R.; Fernandes, C. A. (IEEE Transactions on Antennas and Propagation, 2019)
Focal-plane reflector feeds with shared aperture are a promising solution for the increasing number of beams required in the Ka -band satellite services. Stringent manufacturing tolerances and coupling between feeds tend to penalize performance, which is aggravated for a dual band. This paper proposes a new design of a shared aperture antenna intended for multispot single-feed-per beam satellite applications that allows recovering single-feed performance, minimizing the usual impact of adjacent feeds on the field distribution and ultimately on the antenna directivity and gain. We present a new focal-plane dual-band Fabry–Pérot cavity antenna (FPCA) design, which allows more reliable fabrication, closer agreement with simulations, and larger bandwidth than the reported solutions. It uses only one double-sided printed frequency-selective surface (FSS) to form the dual-band FPCA, and it is fed through a novel arrangement of double-layer slots in the FPCA-printed ground plane. This favors impedance matching and higher isolation between adjacent feeds. The effectiveness of the solution is experimentally demonstrated for a single-feed Ka -band (20 and 30 GHz) prototype. The generalization for a complete multifeed configuration with filters is shown by full-wave simulations. The decoupling slots on the FPCA ground plane enable restoring single-feed performance in the multifeed system, over the bandwidth of interest.